Nurse-Led Telephonic Palliative Care: A Case-Based Series of a Novel Model of Palliative Care Delivery. Issue 2 (14th April 2022) - Yamarik, Rebecca L.; Tan, Audrey; Brody, Abraham A.; Curtis, Jennifer; Chiu, Laraine; Bouillon-Minois, Jean-Baptiste; Grudzen, Corita R.
Abstract : Americans near the end of life experience high rates of nonbeneficial, burdensome, and preventable hospital-based care. If patients' goals of care are unknown or unclear, they have higher rates of hospitalization at the end of life. The demand for palliative care has grown exponentially because of its impact on quality of life, symptom burden, and resource use, requiring the development of new palliative care models. Nurses' holistic outlook and patient-centered focus make them ideal to deliver telephonic palliative care. This article discusses 4 cases delivered by a nurse-led telephonic palliative care program, a part of the Emergency Medicine Palliative Care Access project, which is a randomized controlled trial comparing outpatient palliative care with nurse-led telephonic case management after an emergency department visit. Telephonic nurses discuss patients' goals, fears, hopes, and concerns regarding their illness and its trajectory that inform decisions for future interventions and treatments. In addition, they share this information with the patients' surrogate decision-makers and clinicians to facilitate care coordination and symptom management. For seriously ill patients, nurses' abilities and expertise, as well as the difficulties of providing care through in-person models of palliative care delivery, make a nurse-led telephonic model an optimal option.